2002
DOI: 10.1046/j.1537-2995.2002.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of platelets in additive solutions: effects of magnesium and/or potassium

Abstract: The combination of Mg(2+) and K(+) gave significantly (p < 0.05) lower platelet CD62 expression in the storage medium than in PAS-2. The effects of these differences on platelet metabolism and in vivo properties remain to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 15 publications
(23 reference statements)
6
67
1
Order By: Relevance
“…[10][11][12] Also, PASs can be formulated to modulate specific PLT characteristics; for example, addition of potassium and magnesium to PAS reduces PLT activation. 13 An observational study showed that the CCI for PLTs stored in plasma had a mean 1-hour CCI of 10.2 6 6.7 versus 10.0 6 6.3 for PLTs stored in a potassium-and magnesium-containing PAS; a solution without these two ingredients had a mean CCI of 8.6 6 6.4 (p < 0.01). 14 Having this in mind, we wondered whether the use of PAS might be able to abrogate the negative effects of PRT on PLT quality, and a four-arm paired study design was developed to allow a good comparison of the various processing, treatment and storage conditions.…”
Section: Resultsmentioning
confidence: 98%
“…[10][11][12] Also, PASs can be formulated to modulate specific PLT characteristics; for example, addition of potassium and magnesium to PAS reduces PLT activation. 13 An observational study showed that the CCI for PLTs stored in plasma had a mean 1-hour CCI of 10.2 6 6.7 versus 10.0 6 6.3 for PLTs stored in a potassium-and magnesium-containing PAS; a solution without these two ingredients had a mean CCI of 8.6 6 6.4 (p < 0.01). 14 Having this in mind, we wondered whether the use of PAS might be able to abrogate the negative effects of PRT on PLT quality, and a four-arm paired study design was developed to allow a good comparison of the various processing, treatment and storage conditions.…”
Section: Resultsmentioning
confidence: 98%
“…Regarding the last limitation, additive solutions have been developed that can attenuate PLT activation. Adding magnesium and potassium ions to the commercial additive solutions PASII and PASIII completely prevented PLT activation, as evidenced by comparable levels of CD62p expression, BMR release, glucose consumption and lactate production (de Wildt-Eggen et al, 2002;Gulliksson et al, 2003;Shanwell et al, 2003). In addition, M-sol, which contains magnesium and potassium ions, reportedly has attenuating effects on PLT activation (Hirayama et al, 2007).…”
Section: Plasma-reduced (Or Concentrated) Plts and Washed Pltsmentioning
confidence: 98%
“…Storing platelets in additive solution containing magnesium and potassium (PASIIIM) improves the functionality of the platelets, as measured by glycolysis, pH, morphology, adenosine triphosphate (ATP), and CD62 expression, [12] and may allow a reduction of the amount of plasma required to be carried over to the final unit, facilitating some methods of viral inactivation and making available greater amounts of plasma for other needs. [13] Platelet additive solution replaces 70-80% of the plasma in the original platelet unit; the final medium contains 20-30% donor plasma.…”
Section: Discussionmentioning
confidence: 99%